2015
DOI: 10.15553/c2015v702a6
|View full text |Cite
|
Sign up to set email alerts
|

Bambusa gurgandii K. M. Wong & M. H. Diep (Poaceae, Bambusoideae), a New Species of Bamboo from Vietnam

Abstract: Bambusa Schreb. (Poaceae, Bambusoideae) is a large and complex tropical and subtropical Asian genus that is currently being taxonomically remodeled through morphological and molecular phylogenetic approaches. The type and type alliance of the genus is, however, morphologically well distinguished. Preliminary documentation suggests there could be some 60-70 species of Bambusa in Vietnam, although confirmation requires more rigorous herbarium-based vouchering. A new species of bamboo belonging to the type allian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 793 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Matching the radar resolution to that of the model, should minimize numerical effects, while focusing on physical features. In particular, the belt and cell features in precipitation fields [18,19] are better simulated with RDA. Higher vertical resolution used in "cube-smoothing" RDA allows also to correct the position of the condensation level, which reduces the phase error.…”
Section: Results Of Radar Data Assimilationmentioning
confidence: 99%
“…Matching the radar resolution to that of the model, should minimize numerical effects, while focusing on physical features. In particular, the belt and cell features in precipitation fields [18,19] are better simulated with RDA. Higher vertical resolution used in "cube-smoothing" RDA allows also to correct the position of the condensation level, which reduces the phase error.…”
Section: Results Of Radar Data Assimilationmentioning
confidence: 99%
“…For example, it has been noted that long term use of cytostatic capecitabine may cause loss of usable fingerprints for identification. 64 Thus, for such patients, as well as for individuals missing an arm, reference templates cannot be generated in biometric systems based on fingerprints. Generally speaking, it is not very likely that a single approach will be satisfactory for airport security and airline safety needs.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies indicated that several freshwater fishes cultivated 127 in fish ponds around the PRD and purchased from local markets all contained DDTs 128 (Cheung et al, 2006), and in particular the Mandarin fish (Siniperca kneri) are of actual 129 concern, which could contain DDTs up to 4.3 times higher (62 µg kg-1 wet wt.) than 130 128, 134, 136, 138, 144, 146, 147, 151, 153, 157, 158 165 (total hexa-PCBs), 173,174,177,179,180,187,190,191 (total hepta-PCBs), 194, 195, 166 199, 203…”
Section: Introduction 77mentioning
confidence: 99%